2017
DOI: 10.1007/s10339-017-0799-4
|View full text |Cite
|
Sign up to set email alerts
|

Time takes space: selective effects of multitasking on concurrent spatial processing

Abstract: Many everyday activities require coordination and monitoring of complex relations of future goals and deadlines. Cognitive offloading may provide an efficient strategy for reducing control demands by representing future goals and deadlines as a pattern of spatial relations. We tested the hypothesis that multiple-task monitoring involves time-to-space transformational processes, and that these spatial effects are selective with greater demands on coordinate (metric) than categorical (nonmetric) spatial relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 38 publications
6
13
0
Order By: Relevance
“…As a direct support for this spatial offloading hypothesis, we have reported several studies (with Swedish and Italian participants) showing that spatial ability and executive functioning are independent predictors of multitasking performance, and that spatial ability predicts multitasking over and beyond executive functioning (Mäntylä, 2013;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, & Mäntylä, 2014;Todorov, Del Missier, Konke, & Mäntylä, 2015).…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…As a direct support for this spatial offloading hypothesis, we have reported several studies (with Swedish and Italian participants) showing that spatial ability and executive functioning are independent predictors of multitasking performance, and that spatial ability predicts multitasking over and beyond executive functioning (Mäntylä, 2013;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, & Mäntylä, 2014;Todorov, Del Missier, Konke, & Mäntylä, 2015).…”
mentioning
confidence: 64%
“…handling objects on a workspace while completing additional spatial tasks). We recently reported a study (Mäntylä et al, 2017), in which participants completed a similar multitasking session, while making concurrent spatial judgments. We expected and found concurrent task costs, suggesting that possibilities for spatial offloading were reduced when the coordination of temporal deadlines was completed under concurrent spatial task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we propose, as in Norman and Shallice's (1986) supervisory attentional system, that learned spatial schemas (or schemata, in Norman and Shallice's theory) enable people to be less dependent on attentional resources. Recent results by Mäntylä and colleagues (e.g., Mäntylä, 2013;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, Konke, & Mäntylä, 2015;Todorov, Kubik, Carelli, Del Missier, & Mäntylä, 2018) seem compatible with this idea. They showed that spatial abilities contribute to multitasking, and that when spatial coding was impeded, multitasking performance dropped.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 78%
“…This idea resonates with similar views of "time-to-space mappings" in other domains of cognitive sciences, which suggest that temporal and spatial processing are closely related (e.g., Gijssels, Bottini, Rueschemeyer, & Casasanto, 2013;Núñez & Cooperrider, 2013;Bonato, Zorzi, & Umiltà, 2012;Dehaene & Brannon, 2011). This "spatial offloading hypothesis" is supported by several studies showing that spatial ability (i.e., mental rotation) and executive functioning (i.e., working memory updating) are independent predictors of multitasking performance and that spatial ability predicts multitasking over and beyond executive functioning (Todorov, Kubik, Carelli, Del Missier, & Mäntylä, 2018;Mäntylä, Coni, Kubik, Todorov, & Del Missier, 2017;Todorov, Del Missier, & Mäntylä, 2014;Mäntylä, 2013;Morgan et al, 2013;Logie et al, 2011). Moreover, it was shown that multitasking, compared with dual tasking, involves an incremental contribution of spatial ability (Kubik, Zimmermann, Del Missier, Frick, & Mäntylä, 2018, 2019 and that concurrent spatial load selectively impairs multitasking performance (Todorov et al, 2018;Mäntylä et al, 2017).…”
Section: Introductionmentioning
confidence: 89%